PEMERIKSAAN LEUCOCYTOZOONOSIS PADA BROILER DAN ITIK MENGGUNAKAN METODE GERUSAN ORGAN DAN HAPUSAN DARAH (EXAMINATION OF LEUCOCYTOZOONOSIS IN BROILERS AND DUCKS USING ORGAN MASHED METHODS AND BLOOD SMEAR *) - Hanafiah, Muhammad; Sulaiman, Rusli; Latif, Nuraini (Jurnal Veteriner; Vol 8 No 2 (2007))
The study has been done to examine Leucocytozoonosis case using organ mashed method in broiler and ducks slaughtered in chickens slaughter house in Banda Aceh Nanggroe Aceh Darussalam. From each of broiler and ducks fifty organs were collected for sample. Before those animals were killed blood smear were taken to find merozoites and gametosites stadium while smashed organs were made to find schizont stadium. The number of schizont of Leucocytozoonosis were analyzed descriptively. Result of research indicate that was higher positive Leucocytozoonosis with mashed method better than blood smear in broiler and duck. T he prevalence of Leucocylozoonosis with blood smear respectively are 30 % and 24 % from broiler while by using organ smashed methods are 58 % and 54 % respectively.
Keywords: Leucocytozoonosis, broiler, duck, mashed, blood smear